Mathematical modeling of injury healing process under the action of an active pharmaceutical ingredient (API) - Palomino I, Alfredo (2019)
In this work we carried out the mathematical modeling of the wound healing process, which is a well documented topic in medical and biological practice; but mathematically speaking there are still too much to be done for a clear understanding of the healing phenomom. Here we contribute to the mathematical modelling by using chemical kinetic concepts and mathematical tools, from which we have been able to formulate a system of ordinary differential equations of initial value, whose solution is presented graphically in front of a case study, where we have tested an active pharmaceutical principle with respect to its effectiveness. Finally, the speed of the healing process for such a case study produced an excellent agreement with experimental data that has been omitted due to confidentiality.